Students’ Acceptance towards Kahoot Application in Mastering Culinary Terminology - Adibah Aishah Md Sahak; Abdul Wafi Abdul Rahman; Mohd Raden Farhan Helmy Raden Ismail; Mohd Akmal Rohiat; Nur Diyana Mohd Yazid; Siti Nurshafiqa Aminudin; Siti Hajar Zakariah (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
Kahoot! is a game-based learning platform used to review students’ knowledge, for formative assessment and provides an opportunity not only to assess students' conceptual understanding but also to build new knowledge through further clarification during or after the game. The objective of this study is to assess the acceptability of culinary students in the use of Kahoot! application for mastery the culinary terminology. This study aimed to identify students' acceptance of learning applications, to identify students' acceptance of Kahoot! use in terms of memory as well as students' level of mastering Kahoot! in the learning process. This study is a descriptive study that used a five-point Likert scale questionnaire as an instrument. A total of 48 second year students from the Catering program were used as the study sample. The collected data were analyzed using Statistical Package for Social Science Version 23.0 for Windows (SPSS). The results show that the aspect of students' level of mastering the culinary terminology using Kahoot! application is high with a mean score of 4.55. Whereas the students’ acceptance of Kahoot! as a learning application, was also high with a mean score of 4.44. Finally, the students’ acceptance of the culinary terminology tested using Kahoot! is high with a mean score of 4.45.